What is dark matter? - Fisher, Peter, 1959- (Princeton frontiers in physics., 2022)
"This concise book introduces readers in the physical sciences (and beyond) to the exciting frontier topic of dark matter - a mysterious, non-luminous form of matter in the universe that is thought to account for about 27% of the mass-energy balance in the universe. Though dark matter has not yet been directly detected, its presence is implied by the fact that gravitational effects observed in galaxies cannot be explained unless they actually contain more matter than can be seen. If dark matter was not present, galaxies would not evolve or behave as they do, and many other lines of evidence from cosmology and astronomy give credence to its existence. Yet, what is dark matter? To answer this question, particle physicists (like the author) are joining in the quest to identify dark matter's true nature via experimental efforts aimed at directly detecting it. Although the book does not end with a grand revelation about the properties of dark matter in response to the title question, the book offers readers a deeper understanding of the current state of the dark matter problem and what a triumph it will be when we do learn something new about what dark matter really is. While cutting-edge research efforts are underway to answer the book's title question, this book brings readers up to speed with how observational astronomers came to know about dark matter; how theoreticians revealed how dark matter shapes the largest structures in our universe through gravity; and how physical scientists across disciplines are navigating the complex and frustrating hunt to reveal the nature of dark matter through the experimental detection of an as-yet-undiscovered dark matter particle"--